2021
DOI: 10.3389/fcell.2021.645641
|View full text |Cite
|
Sign up to set email alerts
|

Expressional and Prognostic Value of S100A16 in Pancreatic Cancer Via Integrated Bioinformatics Analyses

Abstract: Studies have shown that the calcium-binding protein family S100 may play a role in the development of pancreatic cancer (PC), but the role of S100A16 in PC is still unknown. In this study, Oncomine was first used to detect the expression level and prognosis of S100A16 in PC and other tumors. The results showed that S100A16 was highly expressed in PC tissues compared with a normal pancreas, and the increased expression level may be related to poor prognosis in PC patients. The TCGA and ICGC RNA-seq data of PC p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…For example, COL11A1 was considered to be a prognostic marker of PDAC and was significantly related to tumor immune infiltration ( 51 ). Additionally, S100A16 was discovered as an important biomarker for the diagnosis and prognosis of PDAC ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, COL11A1 was considered to be a prognostic marker of PDAC and was significantly related to tumor immune infiltration ( 51 ). Additionally, S100A16 was discovered as an important biomarker for the diagnosis and prognosis of PDAC ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, we identified S100A16 using multiple criteria, including its association with glioma, functional validation, and overall survival analysis. S100A16 is involved in various tumors, such as colorectal cancer, bladder cancer, pancreatic cancer, lung adenocarcinoma, cervical cancer, leukemia, and gastric cancer [37][38][39][40][41][42][43]. According to the CGGA database, S100A16 closely correlates with the survival rate of patients with primary gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…S100A16 enhances the progression and metastasis of PAAD via FGF19 mediated AKT and ERK1/2 pathway (30). The study of Gangping Tu, et al showed that in comparison with the normal pancreas, S100A16 was highly expressed in tissues with PAAD, and the increase of its expression level may be correlated with an unfavorable prognosis of PAAD patients (35). CD40 is a cell surface member of the tumor necrosis factor (TNF) receptor superfamily.…”
Section: Discussionmentioning
confidence: 99%